2013
DOI: 10.1038/nprot.2013.021
|View full text |Cite
|
Sign up to set email alerts
|

Building a morbidostat: an automated continuous-culture device for studying bacterial drug resistance under dynamically sustained drug inhibition

Abstract: We present a protocol for building and operating an automated fluidic system for continuous culture that we call the "morbidostat". The morbidostat is used to follow evolution of microbial drug resistance in real time. Instead of exposing bacteria to predetermined drug environments, the morbidostat constantly measures the growth rates of evolving microbial populations and dynamically adjusts drug concentrations inside culture vials in order to maintain a constant drug induced inhibition. The growth rate measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(150 citation statements)
references
References 11 publications
2
135
0
13
Order By: Relevance
“…We performed three replicated experiments (two for strain PA77 with four and five parallel cultures and one experiment for strain PA83 with nine parallel cultures) selecting for colistin resistance mutations in a modified morbidostat setup (26). Our morbidostat can culture 15 populations in parallel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed three replicated experiments (two for strain PA77 with four and five parallel cultures and one experiment for strain PA83 with nine parallel cultures) selecting for colistin resistance mutations in a modified morbidostat setup (26). Our morbidostat can culture 15 populations in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…The morbidostat continuously adjusts drug concentration such that bacteria are always challenged to evolve resistance against the drug while still being able to grow (22,26). In contrast to transposon knockout screens for polymyxin resistance (39), direct selection for resistance by the morbidostat and whole-genome deep sequencing allows the unbiased detection of loss-of-function as well as gain-of-function mutations associated with resistance (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical uncertainty estimates on growth rate were propagated from the uncertainty on measurements of OD (see Table S1 in the supplemental material). In order to confirm that the growth rates calculated from this method were indeed increases in exponential growth rate rather than decreases in the lag phase, we developed a real-time growth curve assay that used a home-built optical density logger (35) in order to monitor population growth. Details of the logger and the procedure are available in the supplemental material.…”
Section: Desulfovibrio Vulgarismentioning
confidence: 99%
“…However, while the mechanisms of resistance are well understood, the population-level dynamics inherent in frequency shifts from sensitivity to resistance are not well understood. There has been some excellent work showing that resistance can be selected for in populations that are in very low-concentration (Ͻ ϽMIC) antibiotic environments (5), and some clever approaches to investigating intermediate mutational steps in the evolution of resistance have been developed (6)(7)(8). For example, using the morbidostat (7), a culturing device that keeps population growth below the maximal growth rate ( max ) by the addition of sublethal doses of an antibiotic, Toprak et al (6) showed that trimethoprim resistance in Escherichia coli increases in a stepwise fashion, with a preponderance of mutations occurring in the folic acid synthesis genes, while doxycycline and chloramphenicol resistance increases more continuously, and mutations promoting resistance are found in membrane proteins and in proteins involved in transcription and translation.…”
mentioning
confidence: 99%